2005
DOI: 10.1158/0008-5472.can-05-1093
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor–Targeted Immunoliposomes Significantly Enhance the Efficacy of Multiple Anticancer Drugs In vivo

Abstract: We previously reported the development of epidermal growth factor receptor (EGFR)-targeted immunoliposomes that bind and internalize in tumor cells which overexpress EGFR and/or mutant EGFR variant III (EGFRvIII), enabling intracellular delivery of potent anticancer agents in vitro. We now describe in vivo proof-of-concept for this approach for the delivery of multiple anticancer drugs in EGFR-overexpressing tumor models. Anti-EGFR immunoliposomes were constructed modularly with FabVfragments of cetuximab (IMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
251
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(257 citation statements)
references
References 30 publications
4
251
1
1
Order By: Relevance
“…p = phosphorylation chemotherapeutics (Vega et al 2003, Mamot et al 2005 and EGFR targeted radioimmonotherapy (Li et al 2004). EGFR targeted toxins is also an interesting approach in cancer therapy (Engebraaten et al 2002, Sampson et al 2008.…”
Section: Fig7mentioning
confidence: 99%
“…p = phosphorylation chemotherapeutics (Vega et al 2003, Mamot et al 2005 and EGFR targeted radioimmonotherapy (Li et al 2004). EGFR targeted toxins is also an interesting approach in cancer therapy (Engebraaten et al 2002, Sampson et al 2008.…”
Section: Fig7mentioning
confidence: 99%
“…The EpCAM-targeted immunoliposomes described here, with their long circulation half-lives, achieved double the uptake of nontargeted liposomes into tumors 24 h after injection, although both types of liposomes showed similar biodistribution patterns for the other major organs. Other investigators have reported that the tumor localization was similar for either targeted or nontargeted liposomes (18,40). Given that both types of liposomes reach solid tumors by the passive targeting mechanism, the reason for the increased tumor localization of the EpCAM-targeted liposomes versus the nontargeted liposomes may be due to both the high affinity of the scFv fragment, for the antigen, its rapid internalization, and its stability, as a high percentage of scFv remains intact after coupling and during 48 h in the body (30).…”
Section: Discussionmentioning
confidence: 86%
“…Long-circulating liposomes seem to be needed for improved tumor localization (17,18,48) and increased antitumor activity (9,17,18,49,50). The EpCAM-targeted immunoliposomes described here, with their long circulation half-lives, achieved double the uptake of nontargeted liposomes into tumors 24 h after injection, although both types of liposomes showed similar biodistribution patterns for the other major organs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Currently, QDs have been applied in the imaging of biological macromolecules and cells both in vitro and in vivo (5)(6)(7). Non-invasive in vivo imaging has been used for the investigation of tumor development (8)(9)(10), early diagnosis of cancer (10), the transportation of drugs in vivo (11), and monitoring of therapeutic responses in vivo (11)(12)(13). These studies have demonstrated the unique advantages of QDs in the imaging of cells both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%